AFATINIB MONOTHERAPY FOR DOUBLE-PRIMARY LOCALLY ADVANCED NON-SMALL CELL LUNG CANCER EXON-21 L861Q MUTATION WITH HISTORY OF COLORECTAL CANCER - Jamnasi, Juli; Yeoh, Rudiyo; Sudibio, Sudibio; Hendrik, Hendrik (Radioterapi & Onkologi Indonesia, 2024)
Introduction: Uncommon mutation exon-21 L861Q is a rare type Non-Small Cell LungCancer (NSCLC). Despite the limited data regarding this type of mutation, Afatinib as one of the oral tyrosine kinase inhibitors (TKI) shows good anti-tumor activity.Clinical Features: A 50-year-old woman with a history of post-operative colorectal cancer (2014) without undergoing chemotherapy and radiotherapy; came in October 2020 with severe dyspnea due to massive pleural effusion with a right lower lung bulky mass. Histopathology in 2014 was a low-grade adenocarcinoma colorectal cancer, while the biopsy of the right lung mass in 2020 was a mucinous adenocarcinoma, ALK-negative, TPS 1.75, and exon-21 L861Q mutation.Intervention and Outcomes: The patient underwent thorax drainage to evacuate pleural effusion fluid. Through multidisciplinary discussions, the patient was recommended to take the oral drug TKI Afatinib 40 mg OD in January 2021. On the 2nd week of taking Afatinib, the patient complained of painful swallowing, mouth sores, sore tongue, and joint pain throughout the body; confirmed to be the side effects of the drug. Complaints diminished with supporting drugs, however, did not resolve completely. CT scan in April 2021 showed a significant reduction in lung mass. Due to severe side effects and drastic weight loss, the Afatinib dose was reduced to 20 mg OD. Radiotherapy was incorporated in her treatment session with IMRT to cover the whole tumor.Discussion: Determining the best treatment to treat the patient was initially difficult due to the raising doubt regarding the correlation between the current lung cancer with her previous history of colorectal cancer. Treating the newer lung mass as primary cancer was obviously different rather than treating lung metastatic colorectal cancer. This issue could then be resolved by incorporating more thorough NGS examination. With the finding of exon-21 L861Q mutation in this patient, Afatinib monotherapy is considered the therapy of choice.